RIPK1 kinase-dependent inflammation and cell death contribute to the pathogenesis of COPD. Issue 4 (3rd April 2023) - Van Eeckhoutte, Hannelore P.; Donovan, Chantal; Kim, Richard Y.; Conlon, Thomas M.; Ansari, Meshal; Khan, Haroon; Jayaraman, Ranjith; Hansbro, Nicole G.; Dondelinger, Yves; Delanghe, Tom; Beal, Allison M.; Geddes, Brad; et al.
Background: Receptor-interacting protein kinase 1 (RIPK1) is a key mediator of regulated cell death (including apoptosis and necroptosis) and inflammation, both drivers of COPD pathogenesis. We aimed to define the contribution of RIPK1 kinase-dependent cell death and inflammation in the pathogenesis of COPD. Methods: We assessed RIPK1 expression in single-cell RNA sequencing (RNA-seq) data from human and mouse lungs, and validated RIPK1 levels in lung tissue of COPD patients via immunohistochemistry. Next, we assessed the consequences of genetic and pharmacological inhibition of RIPK1 kinase activity in experimental COPD, using Ripk1 S25D/S25D kinase-deficient mice and the RIPK1 kinase inhibitor GSK′547. Results: RIPK1 expression increased in alveolar type 1 (AT1), AT2, ciliated and neuroendocrine cells in human COPD. RIPK1 protein levels were significantly increased in airway epithelium of COPD patients compared with never-smokers and smokers without airflow limitation. In mice, exposure to cigarette smoke (CS) increased Ripk1 expression similarly in AT2 cells, and further in alveolar macrophages and T-cells. Genetic and/or pharmacological inhibition of RIPK1 kinase activity significantly attenuated airway inflammation upon acute and subacute CS exposure, as well as airway remodelling, emphysema, and apoptotic and necroptotic cell death upon chronic CS exposure. Similarly, pharmacological RIPK1 kinase inhibition significantly attenuated elastase-induced emphysema and lung function decline. Finally, RNA-seq on lung tissue of CS-exposed mice revealed downregulation of cell death and inflammatory pathways upon pharmacological RIPK1 kinase inhibition. Conclusions: RIPK1 kinase inhibition is protective in experimental models of COPD and may represent a novel promising therapeutic approach. Inhibition of RIPK1 kinase in experimental COPD attenuates crucial hallmarks of the disease, including airway remodelling and emphysema. This protective effect is due to reduced pulmonary inflammation and blocking of RIPK1 kinase-dependent cell death. http://bit.ly/3GX2Ly6